Davidson on Keynes and Others - A Rejoinder - Peter Spahn (Intervention. European Journal of Economics and Economic Policies, 2008)
First paragraph: It is, no doubt, impressive to see that Professor Davidson is able to gather from a mere twopage text what the head of its author is »filled up with« (he uses this expression twice). Having read many books and articles written by Paul Davidson I, for my part, would not dare to design such an assessment. Given the page restriction, I did not intend to embark on an indepth discussion of his latest book on Keynes. Instead, I thought of a more or less informed reader of my review to whom I offered some remarks on the contents of the book.
Keywords: 330